A review on the prospect of wind power as an alternative source of energy in Malaysia - Ashwindran, S. N.; Azizuddin, Abd Aziz; Oumer, A. N.; Muhamad Zuhairi, Sulaiman (IOP Publishing, 2021)
Fossil fuels has dictated the energy sector for several decades, rising as the primary and prominent source of energy production for various sector of industries namely electricity (power), transportation, manufacturing and others. However, extensive usage of fossil fuels majorly contributed to pollution issues and degradation of the environment. Hence, governments and research agencies are providing supports and resources to facilitate the growth of renewable energy sector (RES). This manuscript provides a brief view of the challenges of wind renewable energy sector in Malaysia relative to geographical wind condition, government policies and challenges in initiation of wind technologies and global perspective of green energy in terms of RER. It is found that data presented by previous researchers on wind speed data are considered unreliable to be utilized for WT power density assessment and design. Notably, wind speed in Malaysia is seasonal based and highly inconsistent. The wind flow pattern and intensity experience by Malaysia are merely an aftereffect of weather change in neighbouring regions. Nevertheless, it is found that selected regions of east-coast peninsular Malaysia and selected region of Sabah and Sarawak is potential for harvesting wind power due to substantial and adequate wind pattern behavior during monsoon season. Therefore, it is evident that geographical wind condition of Malaysia is appropriate for wind power devices as a form of RER in green energy sector of Malaysia. However, it is also found that fundamental design modification is required on conventional design of WT in terms of blade morphology and configuration in order to adapt to unsteady monsoon wind speed pattern.